The balance sheet identity model : testing ordinary least square assumptions using Malaysian market / Merani Che Ali - Che Ali, Merani (2002)
Models based on a relation between market value and book values employing balance sheet variables are used continuously in the accounting research literature. The basic model is well known as The Balance Sheet Identity model as first mentioned by Landsman in 1986. Among other researchers who have based their work on this model are Kane and Unal (1990), Shevlin (1991), Gopalakrishnan and Sugrue (1993), McCarthy and Schneider (1995), Jennings et al (1996) and Pfeiffer (1998). However, all of them were facing several econometric problems when estimating the model. Basically, these problems are related to the procedure for the estimation of the parameters of a population regression line provided by the ordinary least squares (OLS). OLS is based on a number of assumptions about the variables and the error term that must be satisfied in order to ensure the interpretations of the regression estimates are valid. This study empirically examines whether the model using Malaysian data will encounter the same econometric problems. In doing so, we tested five common assumptions namely, normality, serial correlation, linearity, heteroscedasticity and multicollinearity. The empirical results of the test reveal that the models using Malaysian data are facing linearity, normality and heteroscedasticity problems.